2019
DOI: 10.1016/j.nicl.2019.101854
|View full text |Cite
|
Sign up to set email alerts
|

Testing the expanded continuum hypothesis of schizophrenia and bipolar disorder. Neural and psychological evidence for shared and distinct mechanisms

Abstract: Despite the traditional view of Schizophrenia (SZ) and Bipolar disorder (BD) as separate diagnostic categories, the validity of such a categorical approach is challenging. In recent years, the hypothesis of a continuum between Schizophrenia (SZ) and Bipolar disorder (BD), postulating a common pathophysiologic mechanism, has been proposed. Although appealing, this unifying hypothesis may be too simplistic when looking at cognitive and affective differences these patients display. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 135 publications
2
41
0
Order By: Relevance
“…As for the bipolar disorder patients in the present study, FC variabilities in these regions and networks did not differ significantly from either of the other groups, which fell in the intermediate range between those of healthy controls and schizophrenia patients (Figures 2 and 3). Thus, we propose that our findings may offer support for the hypothesis of a psychosis continuum between schizophrenia and bipolar disorder, with more severe brain deficits and disabling symptoms in schizophrenia compared to bipolar disorder (63,64); moreover, changes in dynamic FC may serve as objective biomarkers for such differences in neuropathology between these two disorders. However, future investigation with a larger sample size and a higher statistical power is required to confirm if these changes would be significant in patients with bipolar disorder, as compared to healthy controls and schizophrenia patients.…”
Section: Discussionsupporting
confidence: 65%
“…As for the bipolar disorder patients in the present study, FC variabilities in these regions and networks did not differ significantly from either of the other groups, which fell in the intermediate range between those of healthy controls and schizophrenia patients (Figures 2 and 3). Thus, we propose that our findings may offer support for the hypothesis of a psychosis continuum between schizophrenia and bipolar disorder, with more severe brain deficits and disabling symptoms in schizophrenia compared to bipolar disorder (63,64); moreover, changes in dynamic FC may serve as objective biomarkers for such differences in neuropathology between these two disorders. However, future investigation with a larger sample size and a higher statistical power is required to confirm if these changes would be significant in patients with bipolar disorder, as compared to healthy controls and schizophrenia patients.…”
Section: Discussionsupporting
confidence: 65%
“…Noto et al (2019) reported that first episode psychosis, which later evolves into schizophrenia and bipolar disorder, is characterized by a cytokine storm which is somewhat more pronounced is subjects who will develop schizophrenia. The expanded continuum hypothesis was recently supported by the study of Sorella et al [3]. They found clear evidence in SCZ and BD of a shared altered network of brain areas (including ventrotemporal, medial parieto-occipital areas, as well as portions of the cerebellum and the middle frontal gyrus), which could represent the neural underpinnings of an altered interpretation of reality connected with psychosis.…”
Section: Introductionmentioning
confidence: 83%
“…The BOLD timeseries were then extracted for eight predefined right sided regions of interest (ROI) using 6 mm radius spheres. These ROIs were the following (MNI coordinates given in brackets): ROI_1 -anterior insula (AI) [38,22,3], ROI_2 -inferior frontal gyrus (IFG) [50,26,16], ROI_3 -middle frontal gyrus (MFG) [36,42,28] corresponding to dorsolateral prefrontal cortex (DLPFC), ROI_4 -frontal eye field (FEF) [31, -5, 58], ROI_5 -anterior cingulate cortex (ACC) [5,45,12], ROI_6 -superior parietal lobe (SPL) [24, -54, 68], ROI_7 -amygdala (AMY) [24, 3, -16] and ROI_8 -hippocampus (HPC) [30, -11, -17].…”
Section: Resting State Mri Acquisition and Analysismentioning
confidence: 99%
“…Strategies proved to be efficacious in regulating emotions inside the lab have increasingly been incorporated in various models of therapy to help clients suffering from dysregulated emotions (e.g. Barlow et al, 2017; Dadomo et al., 2016; Grecucci et al, 2015, 2017; Pappaianni et al., 2019; Sorella et al., 2019). Unfortunately, some relevant aspects of what is regulated when we regulate emotional responses are still not clear, and the application of principles and methods of the science of emotion regulation inside the consulting room are still based on communi sensu and not on scientific based prescriptions.…”
Section: Discussionmentioning
confidence: 99%